Literature Review: Alteration in the Age of Menarche Among Indonesian Adolescent - Sekar Ayu Putri; Winda Nadya; Kania Rizqita Dewi; Chahya Kharin Herbawani (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: There are around 900 million adolescent girls who experience early menarche and 85% of them live in developing countries. Objectives: This study aims to knowing the alteration in the age of menarche in among Indonesian adolescent and how pornography can affect it. Research Metodes: This type of research is narrative review which used articles from databases Google Scholar, Garudan, and Pubmed. Results: The result showed that there was alteration in the age of menarche among Indonesian adolescent. These changes are determined by many factors, one of which is exposure to mass media and pornography. Exposure to pornography can affects the condition of the adolescent body, that is stimulating the reproductive and genital systems to mature more quickly, which is causing the reproductive system to mature more quickly and causing menarche. Conclusion: Exposure to pornography causes changes in the age of menarche. Exposure to pornography stimulates the reproductive and genital systems, causing faster maturation. This acceleration of maturation affects the production of sex hormones, causing early menarche. Keywords: Menarche; Menstruation; Pornography; Age; Adolescent